Pengaruh Perceived Organizational Support dan Proactive Personality terhadap Employee Creativity yang Dimediasi oleh Meaning of Work - Muhamad Sarul; Jeliteng Pribadi (Manajemen Inovasi Bisnis dan Strategi, 2023)
A company must pay attention to employee creativity to advance the company. Employee creativity is the ability to create and use new ideas that are useful for the company. Several factors that can affect employee creativity are perceived organizational support, proactive personality, and meaning of work. This study aims to determine the effect of perceived organizational support and proactive personality on employee creativity mediated by meaning of work at Kyriad Muraya Hotel. This study uses primary data obtained by purposive sampling of 86 out of 110 Kyriad Muraya Hotel employees. To answer the hypothesis that connects the independent and dependent variables in the proposed research model, this study uses the Multiple Regression Analysis method using Statistical Package for the Social Sciences (SPSS) software. Meanwhile, the influence of the mediating effect (intervening) is measured by conducting the Sobel test using the Sobel calculator. The results showed that perceived organizational support, proactive personality and meaning of work have a positive and significant effect on employee creativity. The results also found that meaning of work partially mediates perceived organizational support and proactive personality on employee creativity.Keywords: Perceived Organizational Support; Proactive Personality; Meaning of Work; Statistical Package for the Social Sciences; Sobel